2017
DOI: 10.1177/1534734617720623
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of the Effect of the Four-Herb Chinese Medicine ANBP on Promoting Mouse Skin Wound Healing

Abstract: Traditional Chinese medicine has great potential to improve wound healing. ANBP, the mixture of 4 Chinese herbs- Agrimoniapilosa, Nelumbonucifera, Boswelliacarteri, and Pollen typhae-is effective in trauma treatment while its mechanism is still elusive. In this study, quantitative proteomics and bioinformatics analyses were performed to decipher the possible roles of ANBP in accelerated wound healing of mouse skin. Among all 3171 identified proteins, 90, 71, 80, and 140 proteins were found to be differently ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…This technique is known for its high throughput, high sensitivity and high precision, and thoroughly and quantitatively analyzes the genre, number and correlation of proteins, by which complicated network and possible regulatory mechanisms are investigated[ 19 - 21 ]. Protein microarray has been gradually applied to research into traditional Chinese medicine (TCM), such as pharmacodynamics and toxicology of Chinese medications[ 22 - 24 ], yet it has rarely been used in the study of acupuncture-moxibustion therapy.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is known for its high throughput, high sensitivity and high precision, and thoroughly and quantitatively analyzes the genre, number and correlation of proteins, by which complicated network and possible regulatory mechanisms are investigated[ 19 - 21 ]. Protein microarray has been gradually applied to research into traditional Chinese medicine (TCM), such as pharmacodynamics and toxicology of Chinese medications[ 22 - 24 ], yet it has rarely been used in the study of acupuncture-moxibustion therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The healing proteome has been studied in different animal models, especially in mice and pigs. These studies showed that proteins with differential expression correspond to receptors, hydrolases, enzymes, immunity, cytoskeletal proteins, transporters, and oxidoreductases (Chen et al, 2017; Sabino et al, 2015). Additionally, in pathogenic processes such as type 2 diabetes and chronic ulcers, where there is an increase in expression levels of proteins related to inflammation and tissue destruction, proteins with differential expression have been identified, most of which relate to angiogenesis, cell death, and inflammation (Eming et al, 2010; Krisp et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that proteins with differential expression correspond to receptors, hydrolases, enzymes, immunity, cytoskeletal proteins, transporters and oxidoreductases (28,29).…”
Section: Discussionmentioning
confidence: 99%